2011
DOI: 10.1002/ls.151
|View full text |Cite
|
Sign up to set email alerts
|

Detailed characterisation of isomers present in polyalphaolefin dimer and the effect of isomeric distribution on bulk properties

Abstract: This study has been conducted with the aim to gain detailed insight into the chemical nature of polyalphaolefin dimer (PAO dimer, C 20 H 42 ). By using gas chromatography/mass spectrometry, a large number of isomers the complex mixture consists of has been identified; the variety of structural motifs ranges from a homologous series of almost linear vicinal dimethyloctadecanes to highly branched isomers such as 6,7-dibutyldodecane. However, the mixture is characterised by the presence of isomers, which exhibit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 11 publications
(14 reference statements)
1
21
0
Order By: Relevance
“…DMOD has the potential to be used as a base insulating liquid because of its desirable physical properties such as high viscosity indices, good thermal and oxidative stabilities, and low toxicity. 41 GTB is an ester molecule with some advantages as a base insulating liquid. Ester liquids are used as insulating liquids in high voltage applications.…”
Section: Computational Detailsmentioning
confidence: 99%
“…DMOD has the potential to be used as a base insulating liquid because of its desirable physical properties such as high viscosity indices, good thermal and oxidative stabilities, and low toxicity. 41 GTB is an ester molecule with some advantages as a base insulating liquid. Ester liquids are used as insulating liquids in high voltage applications.…”
Section: Computational Detailsmentioning
confidence: 99%
“…It turns out that the base oil composition does not underlie significant fluctuations; only the isomeric distribution within the PAO fraction may vary. However, these variations should not influence the base oil's properties and are therefore not taken into consideration …”
Section: Resultsmentioning
confidence: 99%
“…Chromatographic studies of hydrogenated dimer show that over 50 different isomers are generated during the reaction. 13,14 Moreover, NMR analyses of dimer and other higher oligomers have shown that all of the skeletal rearrangement may occur at the dimerization stage, and much analytical work has focused on the dimer fraction. 15 A more detailed reaction mechanism for the origin of multiple skeletal isomers in the polymerization of 1-decene has been reported by J. C. Gee et al…”
Section: Introductionmentioning
confidence: 99%